(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article analyzes valence problems in modern German syntax. They tried to develop a system of basic sentence models based on the structural diagrams built on the basis of the syntactic valency of the predicate verb. Later, after establishing the structural diagram, an attempt was made to interpret it meaningfully.